The Role of Internal Cash Control and Separation of Accounting Functions in Reducing the Risk of Financial Fraud in Savings and Loan Cooperatives in Central Java - Kimsen Kimsen; Triana Zuhrotun Aulia; Eko Sudarmanto (West Science Interdisciplinary Studies, 2026)
Financial fraud remains a major challenge for savings and loan cooperatives, particularly in maintaining sound financial governance and member trust. This study examines the role of internal cash control and the separation of accounting functions in reducing the risk of financial fraud in savings and loan cooperatives in Central Java. A quantitative research approach was employed using data collected from 100 cooperative employees through structured questionnaires measured on a Likert scale. The data were analyzed using multiple linear regression with SPSS version 25. The results show that internal cash control has a significant negative effect on the risk of financial fraud, indicating that stronger cash control mechanisms reduce opportunities for misappropriation. The separation of accounting functions also has a significant negative effect on fraud risk, demonstrating the importance of clear segregation of duties in preventing unethical behavior. Simultaneously, both variables significantly influence the reduction of financial fraud risk in savings and loan cooperatives. These findings highlight the critical role of effective internal control systems in strengthening financial integrity and sustainability within cooperative institutions.